Propuesta de diseño de una planta de tratamiento de los efluentes para minimizar la contaminación ambiental, del Camal Municipal de la parroquia Sigchos, cantón Sigchos, provincia de Cotopaxi - Carasayo Chacha, Segundo David (2013)
In the production process of the municipal slaughterhouse of Sigchos town, solidand liquid waste is generated, both of organic origin and nature which are notproperly utilized or treated, being discharged directly into the sewer system. The Sigchos town slaughterhouse has adequate infrastructure but unfortunately does not have any treatment for effluents coming out at the time of animal slaughter, this creates environmental problems that end up in altering the health of the population and the environment atmosphere. The effluents are discharged directly to the sewer and flow for several kilometers to the Toachi River, causing the death of aquatic flora and fauna of this hydric resource. The Town´s slaughterhouse processes 9 heads of cattle a week distributed as follows: Mondays, Tuesdays and Thursdays none animals are slaughtered on Wednesdays one cattle on Friday two cattle, on Saturday two cattle and on Sunday four cattle in these days the water is high blood, dregs, guts pollution, etc....